The digital reinminbi: monetary sovereignty and technology for the service of the New Projectment Economy - Jabbour, Elias Marco Khalil; Kosinski, Daniel Santos (GEOUSP Espaço e Tempo (Online), 2022)
Perhaps no unit of analysis is as bearer of new research possibilities as the development process of the People's Republic of China. This assertion is justified by the immense impact, by the aforementioned development process, in its territory verified over the last 40 years. The objective of this paper, therefore, perceiving China as a scientific frontier to be better faced by Geography, is to observe the role of the so-called Chinese digital currency, the e-reinminbi as an instrument of direct State intervention in the territory. Wide possibilities of using monetary sovereignty and technology at the service of what has been called the New Projectment Economy have been opened up with the emergence of this digital currency.